PRODUCT PHOTO SUPERVISION AND INTProduct Photo Supervision and Integration in Digital Based Catalog Content for Bandeng Radit UMKMEGRATION IN DIGITAL BASED CATALOG CONTENT FOR BANDENG RADIT UMKM - Suminto, Miftahul Adi; Renzina, Yudha Delonix; Fitrani, Laqma Dica; Yuniar, Alfian Bekti; Rafi, Altha Muhammad (Institut Teknologi Nasional, Bandung, 2025)
This activity was carried out as an effort to improve the ability of Bandeng Radit MSMEs to produce high-quality product photos and integrate them into digital catalog content, which is used as a promotional strategy on social media and digital catalog-based product information content. The main problems faced by partners are limited skills in lighting techniques, visual composition, and the use of digital platforms to market processed products such as presto milkfish, milkfish otak-otak, and grilled milkfish. Training participants were introduced to product photography techniques using smartphones through the Strobist Technique approach, namely the use of artificial light sources such as external flashes and portable softboxes to produce professional lighting in product photos. This activity was carried out using a participatory workshop method that included counseling on basic product photography theory, demonstrations of lighting techniques, shooting practice, editing techniques using applications, and integration of photo results into digital catalogs through the Figma application. Lightroom Mobile the training results showed significant improvements in technical skills, understanding of visual aesthetics, and basic understanding of digital promotion. Product photos produced by partners became more visually consistent, had balanced lighting, and were able to strengthen the brand image of Bandeng Radit MSMEs. This activity also contributes to empowering the local economy based on digitalization and serves as an applied training model for developing the capacity of MSMEs in the creative culinary sector.